Pengaruh KIE Terhadap Tingkat Pengetahuan Pasangan Usia Subur Dalam Pemakaian Alat Kontrasepsi Jangka Panjang (MKJP) Sebagai Bentuk Layanan Prima Di Puskesmas Kenten Laut Kab. Banyuasin Tahun 2024 - Desi Hariani; Elvina Indah Syafriani2; Yulia (STIKes Budi Mulia Sriwijaya, 2025)
ABSTRAK ABSTACK The long-term contraceptive method (MKJP) is a form of contraception that is used for a long time, effectively and efficiently to delay births of more than 3 years. Some of the factors that hinder the achievement of MKJP acceptors are the lack of knowledge, interest and willingness of PUS in the use of MKJP contraceptives, so that people are afraid to use MKJP. The purpose of this study is to study the effect of counseling on the level of PUS knowledge in the use of long-term contraceptive methods (MKJP). This type of research is Quasy Exsperiment with the One Group Pretest Posttest Design approach. This research was conducted at the Kenten Laut Health Center, Banyuasin Regency in 2024. Sampling technique by Purposive Sampling. Based on the formula used, the sample in this study was 28 people. The average level of knowledge of couples of childbearing age (PUS) before being given KIE about MKJP is mean 6.6714 and SD 1.6426 Average level of knowledge of PUS in the use of long-term contraceptive methods (MKJP). This type of research is Quasy Exsperiment with the One Group Pretest Posttest Design approach. This research was conducted at the Kenten Laut Health Center, Banyuasin Regency in 2024. Sampling technique by Purposive Sampling. Based on the formula used, the sample in this study was 28 people. The average level of knowledge of couples of childbearing age (PUS) before being given KIE about MKJP is mean 6.6714 and SD 1.6426 The average level of knowledge of PUS after being given KIE is mean 14.428 and SD 3.686. The results of the dependent T test obtained a value of ρ = <.0001. It can be concluded that there is an influence of communication, information and education (KIE) on the level of knowledge, understanding and willingness of couples of childbearing age in the selection of long-term contraceptives (MKJP) Keywords: Information Communication and Education, Knowledge Level, Long- Term Contraceptive Methods